Differences in root canal system configuration in human permanent teeth within different age groups. (17th February 2018) - Martins, J. N. R.; Ordinola‐Zapata, R.; Marques, D.; Francisco, H.; Caramês, J.
Abstract: Aim: To analyse the differences in root canal system configuration in patients belonging to different age groups using cone beam computed tomography (CBCT) technology. Methodology: CBCT examinations from a pre‐existing database were accessed. Patients were divided according to age groups: '≤20 years', '21–40 years', '41–60 years' and '≥61 years'. Each group included tooth data regarding their root canal system configurations according to the Vertucci classification and its supplementary configurations. Cohen kappa coefficient of agreement was calculated to evaluate observer reliability. Results: Overall 12 325 teeth from 670 patients were included. Most of the root groups had higher or equal prevalence of Vertucci type I configurations in the younger groups whilst presenting a greater tendency for multiple root canal system configurations in older patients, mainly Vertucci type II in both maxillary and mandibular second premolars and in the distal root of the mandibular first molar. The Cohen kappa coefficient of agreement was 89.4 ± 1.8%. Conclusion: Clinicians should be aware that the root canal system configuration changes over a lifetime. In this study, the most affected teeth were the second premolars and the distal root of mandibular first molars.